2018
DOI: 10.1002/nbm.3944
|View full text |Cite
|
Sign up to set email alerts
|

Size‐adaptable 13‐channel receive array for brain MRI in human neonates at 3 T

Abstract: Neonatal brain injury suffered by preterm infants and newborns with some medical conditions can cause significant neurodevelopmental disabilities. MRI is a preferred method to detect these accidents and perform in vivo evaluation of the brain. However, the commercial availability and optimality of receive coils for the neonatal brain is limited, which in many cases leads to images lacking in quality. As extensively demonstrated, receive arrays closely positioned around the scanned part provide images with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…This issue requires adapting the acquisition sequences to obtain relevant and sufficient image contrast. Using dedicated coils, with optimized size in relation to the size of the head to be imaged, also makes it possible to maximize the signal‐to‐noise ratio (SNR) in the images 28–30 with a gain greater than x2, depending on the brain regions and their proximity to the coil elements. Considering dedicated image postprocessing tools is also required to deal with the signal and contrast specificities of newborn images.…”
Section: An Overview Of Early Developmental Mechanismsmentioning
confidence: 99%
“…This issue requires adapting the acquisition sequences to obtain relevant and sufficient image contrast. Using dedicated coils, with optimized size in relation to the size of the head to be imaged, also makes it possible to maximize the signal‐to‐noise ratio (SNR) in the images 28–30 with a gain greater than x2, depending on the brain regions and their proximity to the coil elements. Considering dedicated image postprocessing tools is also required to deal with the signal and contrast specificities of newborn images.…”
Section: An Overview Of Early Developmental Mechanismsmentioning
confidence: 99%
“…In this regard, MRI acquisition settings including the specific head coil and scanning parameters should be adjusted for neonates. In detail, a neonatal head coil with appropriate size and high signal-to-noise ratio, as well as the use of appropriate scanning parameters (e.g., smaller FOV, longer repetition time and echo time than adult scanning) would facilitate the signal acquisition [23,25]. By comparing the three workflows, we found that slight adjustment for skull stripping would remarkably affect the calculations of regional brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…In details, a neonatal head coil with appropriate size and high signal-to-noise ratio, as well as the use of appropriate scanning parameters (e.g. smaller FOV, longer repetition time and echo time than adult scanning) would facilitate the signal acquisition [23,25].…”
Section: Discussionmentioning
confidence: 99%